Culture-Based Risk Management (Experimental Study on Saving and Loan Cooperative in Badung Regency) - I Wayan Suartana; I Ketut Jati (Institute for Research and Community Services Udayana University, 2017)
This research aims to provide an overview of the application of risk management based on local cultural values conducted by Saving and Loan Cooperative (SLC) in Badung Regency as the main component in the implementation of good corporate governance by optimising the local cultural values such as Tri Hita Karana and Catur Purusha Artha. By putting forward the local cultural values, the Saving and Loan Cooperative (SLC) is expected to grow and flourish with the internalisation of strong cultural values leading to good and appropriate corporate governance. This research is conducted by an experimental study using questionnaire as the media. The research sample is the Saving and Loan Cooperative's employees in Badung Regency. The results confirm our hypothesis with a total of 56 respondents. The total number of respondents are 56 (fifty-six) people. The test results show that Tri Hita Karana and Catur Purusha Artha individually strengthen the risk management of Saving and Loans Cooperative. Keywords: Risk Management, Saving and Loan Cooperative, Tri Hita Karana, Catur Purusha Artha